Timeout: The Role of Family-Friendly Policies in Business Start-Up Among Mothers. (July 2023) - Markowska, Magdalena; Ahl, Helene; Naldi, Lucia
This article explores why an increasing number of Swedish mothers are becoming entrepreneurs; this choice appears counterintuitive given the prevailing social welfare system prioritizes the rights of employed women. Using an interpretative stance, we analyzed the life stories of 18 Swedish mothers who created new ventures while caring for young children. The value of the time afforded by parental leave policies was identified as vital to the business creation process. Hence, we argue that time is a critical entrepreneurship-relevant resource; this is illustrated by the positive effect of the Swedish welfare system upon entrepreneurship entry and the timing of this decision.